Deceptive Echoes in Christie’s “The Mystery of the Blue Jar” - Kandel, Churamoni (Kaumodaki: Journal of Multidisciplinary Studies, 2026)
This research article examines and analyzes how Agatha Christie employs deceptive sound as a central narrative device in her short story “The Mystery of the Blue Jar.” Christie constructs an acoustic illusion that shapes perception, directs suspicion, and manipulates both the protagonist and the reader. The repeated cry, “Help! Murder! Help!” functions not only as a mysterious disturbance but also as an engine of psychological tension. This research employs Sound Studies and Cognitive Narratology as tools to explore how Christie turns hearing into an unreliable sense. The protagonist believes in the authenticity of the cry because sound seems immediate, vivid, and commanding. Yet the story gradually exposes the instability of auditory perception. This instability becomes the foundation of narrative suspense. This study relies on qualitative close reading of the primary text, supported by selective secondary criticism related to sensory studies, narrative cognition, and detective-fiction techniques. The analysis portrays how Christie employs repetition, isolation, sensory contradiction, and controlled auditory staging to produce confusion. The cry becomes a tool of manipulation rather than a clue to real violence. Through this technique, Christie portrays how sound influences human cognition easily, especially when the listener expects meaning and danger. It becomes an instrument of deception as powerful as visual misdirection.